An experimental evaluation method of drilling fluid lost control efficiency considering loss types - Zhang, Jingyi; Kang, Yili; Deng, Yunhui; Xu, Chengyuan; Yan, Xiaopeng; Lin, Chong; Cui, Xiaojiang (Frontiers in Physics, 2023)
There are serious drilling fluid loss problems in fractured reservoirs during drilling and completion. Indoor evaluation of drilling fluid lost control effect is an important basis for on-site plugging formula design, but there are some problems in drilling fluid lost control evaluation, such as the inability to evaluate specific loss types. Therefore, based on the classification of loss causes, this paper defines the main control factors of drilling fluid lost control efficiency of different loss types, and puts forward a method for judging loss types. The influence of fracture module and experimental steps on drilling fluid lost control efficiency was evaluated through laboratory experiments. Based on the analysis method of indoor and field drilling fluid lost control efficiency, the best laboratory experimental conditions of different loss types were determined, and then the experimental evaluation method of drilling fluid lost control efficiency considering various loss types was established. This method can comprehensively evaluate and grade the lost control ability of the plugging formula. Through the verification in Block K of Tarim Basin, the test results are closer to the field lost control results, and the evaluation results of drilling fluid lost control efficiency are better, which can guide the field leakage control evaluation.